Pengaruh Variasi Konsentrasi Larutan Pembersih Lantai Terhadap Pencapaian Standar Baku Mutu Kepadatan Kuman di IGD RSUD PANDEGA Kabupaten Pangandaran - hari, Munto (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2024)
The use of disinfectants to clean floors in hospital patient care areas is an effort carried out routinely to ensure environmental quality meets predetermined requirements. Floor cleaning for the period July-December 2023 in the Emergency Room (IGD) of the Regional General Hospital (RSUD)